2001
DOI: 10.1161/01.str.32.6.1304
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Motor Responses to Focal Transcranial Magnetic Stimulation in Healthy Subjects and Acute-Stroke Patients

Abstract: Background and Purpose-Prevalence and characteristics of ipsilateral upper limb motor-evoked potentials (MEPs) elicited by focal transcranial magnetic stimulation (TMS) were compared in healthy subjects and patients with acute stroke. Methods-Sixteen healthy subjects and 25 patients with acute stroke underwent focal TMS at maximum stimulator output over motor and premotor cortices. If present, MEPs evoked in muscles ipsilateral to TMS were analyzed for latency, amplitude, shape, and center of gravity (ie, pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
103
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 24 publications
10
103
1
2
Order By: Relevance
“…In non-impaired individuals, ipsilateral MEPs in the PMJ muscles are typically only about 20% of the contralateral MEP amplitude (MacKinnon et al 2004), which corresponds to a laterality index score of approximately +0.67. Previous studies have shown that ipsilateral MEPs are elicited more frequently in stroke survivors than in able-bodied individuals (Alagona et al 2001). In the present study, ipsilateral MEPs were evoked significantly more often in the moderate-severe group than in the mild-moderate group.…”
Section: Ipsilateral Mep Prevalencesupporting
confidence: 58%
See 1 more Smart Citation
“…In non-impaired individuals, ipsilateral MEPs in the PMJ muscles are typically only about 20% of the contralateral MEP amplitude (MacKinnon et al 2004), which corresponds to a laterality index score of approximately +0.67. Previous studies have shown that ipsilateral MEPs are elicited more frequently in stroke survivors than in able-bodied individuals (Alagona et al 2001). In the present study, ipsilateral MEPs were evoked significantly more often in the moderate-severe group than in the mild-moderate group.…”
Section: Ipsilateral Mep Prevalencesupporting
confidence: 58%
“…This finding has been demonstrated using functional magnetic resonance imaging (fMRI) (Cao et al 1998;Carey et al 2002;Cramer et al 1997;Feydy et al 2002;Marshall et al 2000;Ward et al 2003), positron emission tomography (PET) (Chollet et al 1991;Honda et al 1997;Weiller et al 1993), electroencephalography (EEG) (Green et al 1999;Kopp et al 1999;Serrien et al 2004;Verleger et al 2003) and transcranial magnetic stimulation (TMS) (Alagona et al 2001;Chen et al 2003;Fujiwara et al 2001;Strens et al 2003;Ward et al 2003). The functional role of this increase in ipsilateral motor cortical activity may differ depending upon whether the lesioned pathway projected to motor neurons controlling the distal, proximal or axial musculature.…”
Section: Introductionmentioning
confidence: 95%
“…Bilateral montage is often used based on the assumption that the movements of the impaired limbs are often associated with a high level of transcallosal inhibition by the hemisphere not affected by the hemisphere being injured [10,20]; some studies conducted with multimodal imaging techniques and mapping, such as fMRIs and TMSs, confirmed the existence of this imbalance of the hemisphere not affected, also called a hemispheric competition model, particularly during the preparation and execution of upperlimb motor acts [21,22], some authors hypothesize that the amount of this imbalance in inter-hemispheric excitability may be positively correlated with the degree of severity of motor disability [10,6]. Lindenberg motor function in the stimulated group, stimulation with simultaneous rehabilitation treatment based on physiotherapy techniques and occupational therapy with compared to the control group; the effects are verifiable even after one week after the end of the treatment; it has also been hypothesized that the magnitude of the electrode may affect the adjacent premotory cortex as well as the anodic somatosensory cortex; similarly, cathodal stimulation may have a similar effect in adjacent structures [19].…”
Section: Discussionmentioning
confidence: 99%
“…Bawa et al (2004) concluded that, in general, forearm and hand muscles in healthy subjects did not show any ipsilateral motor evoked potentials. However, in poststroke patients, ipsilateral responses have been recorded (Alagona et al 2001).…”
Section: Effects Of Tdcs Applied To Ipsilateral Hand Motor Cortexmentioning
confidence: 99%